AB0587 Safety and efficacy of abatacept(ABA) demonstrated in patients with rheumatoid arthritis(RA); 4-year data from phase III open-label, multicenter, long-term extension trial. (23rd January 2014) - Tanaka, Y.; Abe, T.; Takeuchi, T.; Yamamoto, A.; Miyasaka, N.
Abstract : Background: The long-term evidence of ABA for RA patients is limited. Objectives: To assess the long-term safety and efficacy of ABA in patients with RA. Methods: This study consisted of 3 cohorts; Phase I (P1, n=13) and P2 (n=178), ABA10mg/kg + MTX or ABA10mg/kg for 192 wks; new patients (N, n=26), intolerant to MTX due to safety reasons (N). All adverse events and efficacy results were recorded. Results: The average exposure and mean disease duration of 217 patients enrolled in this study was 2.86 and 9.1±7.1 (years), respectively. In total 74.2% patients completed 192 wks period. There was no specific adverse event increased with ABA. The most common AE was nasopharyngitis 56.7%, 46.6 per year of patients. One patient (0.5%) died because of pancreatic carcinoma (causal relationship to study drug:possible). ACR20, DAS28-CRP<2.6, SDAI remission (≤3.3) and Low disease activity (LDA) (≤11) achieved patients ratio increased and maintained steadily and 80.2, 44.7, 12.9 and 52.1% were scored at wks 192, respectively, (Last Observation Carried Forward: LOCF) by the treatment with ABA. Conclusions: During this study, ABA was well tolerated and its efficacy sustained throughout 192 weeks. Disclosure of Interest: None Declared